Who Bears Responsibility for the Provision of Security: The State or You? - Olaf J. de Groot; Hella Engerer (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
When defining the absence of a threat as an economic good, it is necessary to define this good using the standard economic typology: is security a private, public, club or common good? We argue in this Policy Briefing that security provision can display characteristics belonging to any of these types of goods. In recent years, we can observe a change from more publicly oriented security provision to privately provided security. That does not, however, take away the responsibility of the state to provide a basic level of security. In addition to that, it is the responsibility of the state to coordinate internationally to deliver international security.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330